Human papillomavirus infection: the efficacy of treatment with inosine pranobex - P V Budanov; A A Churganova; K R Bakhtiyarov; A N Strizhakov (IP Berlin A.V., 2015)
The high frequency of the spread of human papillomavirus and a high risk of recurrence associated diseases require the search for effective therapies. The analysis of quality clinical trials showed data on the efficacy, tolerability of treatment. Our study demonstrates higher efficiency destructive methods in conjunction with the system using Isoprinosine. Even Isoprinosine mono therapy's efficiency reaches 68%.